Some common fixed point theorem for geraghty’s type contraction mapping with two T-metrics in T-metric spaces with graph - Chaiporn Thangthong (2020)
© 2020 by TJM. All rights reserved. The purpose of this paper is to present some existence and uniqueness results for common fixed point theorems for Geraghty’s type contraction mappings with two T-metrics in T-metric spaces endowed with a directed graph. In addition, Our results generalize those presented in [J. Martínez-Moreno, W. Sintunavarat, Y.J. Cho, Common fixed point theorems for Geraghty’s type contraction mappings using the monotone property with two metrics, Fixed Point Theory Appl. 2015 (2015) 174].